(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This thesis examines the impact of mobile applications and microlearning modules on the effectiveness and activity of students in learning SCIENCE subjects. Microlearning technology involves the gradual formation of knowledge by dividing the educational process into small, easily digestible short segments. Mobile applications allow students to access these modules anywhere and at any time. The study will scientifically examine the impact of short-form digital content on motivation, knowledge retention, personalized learning, and independent research skills.